India Biotech Revolution: The Approval of Genome-Edited Rice - Naveen Kumar; Ajay Singh; Priyansha; Puja Rani Sarkar; Bharat Sharma; Subodh Kumar; Neeraj K. Aggarwal; Aditi Arya (The Bioscan, 2025)
India has reached a significant global milestone by becoming the first country to approve genome-edited rice cultivars for commercial use. The newly introduced varieties, DRR Dhan 100 (Kamala) and Pusa DST Rice 1, developed through advanced genome editing technologies, offer notable improvements in yield and climate resilience. DRR Dhan 100 matures faster and delivers a 25% increase in yield, while Pusa DST Rice 1 boosts productivity by up to 30% in saline and alkaline soils. Tailored for cultivation in regions such as Andhra Pradesh and Telangana, these breakthroughs mark a major step forward in promoting climate-smart agriculture and sustainable rice production in India.